2018
DOI: 10.3892/ijo.2018.4629
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of lncRNA EGFR‑AS1 is associated with a poor prognosis and promotes chemotherapy resistance in non‑small cell lung cancer

Abstract: Chemoresistance is one of the most important biological elements affecting the progression and prognosis of cancer. Long non-coding RNAs (lncRNAs) are important regulators and are aberrantly expressed in various types of cancer in humans, including non-small cell lung cancer (NSCLC). The present study aimed to investigate the effect of lncRNAs on NSCLC resistance to chemotherapy. The relative expression level of epidermal growth factor receptor antisense RNA 1 (EGFR-AS1) was quantified by reverse transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Previous studies have revealed that altered expression of lncRNAs is associated with the development and progression of human malignant tumors, including lung and liver cancer, osteosarcoma, glioblastoma and as well as other types of cancer (811). Furthermore, lncRNAs can act as oncogenes or tumor suppressor genes, modulating the progression of NSCLC and affecting the overall survival (OS) of NSCLC patients (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that altered expression of lncRNAs is associated with the development and progression of human malignant tumors, including lung and liver cancer, osteosarcoma, glioblastoma and as well as other types of cancer (811). Furthermore, lncRNAs can act as oncogenes or tumor suppressor genes, modulating the progression of NSCLC and affecting the overall survival (OS) of NSCLC patients (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed both miRNAs were tumor suppressors and downregulated in tumor samples. In addition to support the ceRNA function, recent studies have reported miRNA sponging activity of EGFR-AS1 47,33 and miR-891b mediated gene regulation [48][49][50] .…”
Section: Discussionmentioning
confidence: 98%
“…Using the online STITCH database, we have found that lncRNA EGFR-AS1 has a positive interaction with PTBP1 and hnRNPs, major players in alternative splicing and essential for the generation of EGFR-A isoform with both transmembrane and tyrosine kinase domain. EGFR-AS1, a lncRNA transcribed from the antisense strand of EGFR, was found to be overexpressed in several cancers 30,11,[31][32][33] . Our study observed a significant upregulation of EGFR-AS1 in oral cancer patients suggesting the oncogenic potential of this lncRNA, which is consistent with above findings.…”
Section: Discussionmentioning
confidence: 99%
“…And lncRNAXIST may have some functions by downregulating miRNA-144. Compared with previous studies,the present study eventually constructed ceRNA [34] network of lncRNA XIST-miRNAs-BAX. We selected top 10 hub RNAs with higher degree through the cytoHubba (Fig.…”
Section: Discussionmentioning
confidence: 99%